Honorários advocatícios sucumbenciais na Justiça do Trabalho e o necessário diálogo normativo - Scalercio, Marcos (2022)
The present research is intended to analyze the legal norms that govern the determination and setting of attorney fees in the Labor Court, emphasizing the need or not of normative dialogue with other legal disciplines, especially Civil Procedure and Constitutional Law for effectiveness. of the labor norm. In this perspective, in addition to the in-depth study of the norm provided for in the labor legislation, the necessary examination of the normative dialogue between procedural labor law and common procedural law in the light of the subsidiary application rule of article 769 of the Consolidation of the Labor Laws. Subsequently, it is also proposed to study the harmonization of the provision of the labor norm with the Constitutional Law with the analysis of the access to Justice and the constitutionality of the collection of succumbential fees of the party that enjoys the benefit of free justice. In order to reach the core of the research, it is intended to clarify that, on the one hand, it is commendable that labor lawyers are given similar treatment to professionals from other legal areas, one cannot do without the construction of legal certainty in the regulation of the figure in the field of labor law